Mitigation Mode of Verbal Action: Verbs with the Meaning ‘to Drink Alcohol’ - O. A. Dimitriyeva (Научный диалог)
The verbs of mitigation (attenuating) mode of action with the semantics ‘to drink alcohol’ formed by a derivational formant под - are discussed. The article continues a series of works devoted to the study of modes of action (e.g., saturating, mitigation, etc.) in relation to the national picture of the world and mentality. The relevance of the study is determined by linguistic and cultural research method. A review of studies on the mitigation mode of verbal action in various aspects is made. Special attention is paid to the analysis of verbs подвыпить, подпить, поддать and their morphological, syntactic and co-occurrence features. Statistical characteristics of the grammatical forms of the reporting verbs are given. It is noted that in modern speech the verb подвыпить is the most common, it is represented in its frequency form of the participle. The scope of the subject of this verb and features of its compatibility with frequentative adverbs are analyzed in detail. Verbs подпить and поддать are used in many grammatical forms and are able to form aspectual correlates due to the argument structure of these verbs. Stereotypes about the culture of drinking are evident in the comparisons and in aspect situations of repetitive actions. Material for the study consists of examples from contemporary literary and media texts from the National corpus of the Russian language.